Brain wave behavior in children with down syndrome following cortical neuromodulation combined with sensorimotor stimulation: observational study. - Lopes, Jamile; Miziara, Isabela; Kahani, Danial; Parreira, Rodolfo; Fonseca, Daniela; Lazzari, Roberta; Cordeiro, Lorraine; Naves, Eduardo; Cimolin, Veronica; Galli, Manuela; Conway, Bernard; Oliveira, Claudia (Physiotherapy Theory & Practice, 2024)
Individuals with Down syndrome (DS) require more time to develop motor and/or cognitive skills. Neuromodulation is used to assist in this development. However, there is a gap in the literature on neurophysiological changes that may occur in the primary motor cortex in individuals with DS following neuromodulation. Our objective was to investigate possible neurophysiological changes in brain wave behavior of the primary motor cortex following the administration of anodal transcranial direct current stimulation combined with sensorimotor training. The study involved 12 participants with DS. EEG equipment was used to investigate brain activity. The participants received neuromodulation involving anodal tDCS for 20 minutes with a current of 1 mA combined with virtual reality (VR) training three times a week for a total of ten sessions. We analyzed EGG signals and 3D movement during a reaching movement of the dominant upper limb before and after the ten-session protocol. Significant differences in event-related desynchronization and event-related synchronization of the alpha and beta rhythms were found throughout the evaluations. Brain mapping revealed reductions in power and frequency, demonstrating changes in the patterns of these rhythms in the cerebral cortex. Revealed reorganization of the behavior of alpha and beta waves, as demonstrated by distribution of synchronization and desynchronization of these waves among the regions of the brain. The results suggest that anodal tDCS promotes the reorganization of brain impulses, redirecting these impulses to the required regions more efficiently and contributing to better motor planning.